SARS-Cov-2 prevalence, transmission, health-related outcomes and control strategies in homeless shelters: systematic review and meta-analysis - Mohsenpour, Amir; Bozorgmehr, Kayvan; Rohleder, Sven; Stratil, Jan; Costa, Diogo (EClinicalMedicine, 2021)
Background - People experiencing homelessness (PEH) may be at risk for COVID19. We synthesised evidence on SARS-Cov-2 infection, transmission, outcomes of disease, effects of non-pharmaceutical interventions (NPI), and the effectiveness of strategies for infection prevention and control (IPC). - Methods - Systematic review of articles, indexed in electronic databases (EMBASE, WHOCovid19, Web of Science), institutional websites and the Norwegian Institute of Public Health's live map of COVID-19 evidence, and published from December 1st, 2019, to March 3rd, 2021. Empirical papers of any study design addressing Covid-19 and health(-related) outcomes in PEH or shelters’ staff were included. (PROSPERO-2020-CRD42020187033) - Findings - Of 536 publications, 37 studies were included (two modelling, 31 observational, four qualitative studies). Random-effect meta-analysis yields a baseline SARS-Cov-2 prevalence of 2•32% (95% Confidence-Interval, 95%CI=1•30-3•34) in PEH and 1•55% (95%CI=0•79-2•31) in staff. In outbreaks, the pooled prevalence increases to 31•59% (95%CI=20•48-42•71) in PEH and 14•80% (95%CI=10•73-18•87) in staff. Main IPC strategies were universal rapid testing, expansion of non-congregate housing, and in-shelter measures (bed spacing, limited staff rotation, reduction in number of residents). - Interpretation - 32% of PEH and 15% staff are infected during outbreaks of SARS-Cov-2 in homeless shelters. Most studies were conducted in the USA. No studies were found quantifying health-related outcomes of NPI. Overview and evaluation of IPC strategies for PEH, a better understanding of disease transmission, and reliable data on PEH within Covid-19 notification systems are needed. Qualitative studies may serve to voice PEH and shelter staff experiences, and guide future evaluations and IPC strategies. - Funding - None.
Gesehen am 03.11.2021